Usefulness of Moringa oleifera seed extract as Coagulant for the production of fresh camel cheese - Fguiri, Imen; Sboui, Amel; Yousfi, Nahed; Arroum, Samira; Dbara, Mohamed; Hammadi, Mohamed; Khorchani, Touhami (Italian Journal of Food Science, 2024)
The current study aimed to enhance the coagulation properties of camel milk using enzymatic extracts derived from Moringa oleifera seeds. Experiments were conducted to evaluate the clotting activities of Moringa extract on camel milk and compare them with cow milk. Our results regarding the characterisation of the enzymatic extract showed an extraction yield of 54.3±1.8%. The optimum coagulation conditions were determined to be pH 5 and a temperature of 55°C. In addition, the enzymes exhibited substantial clotting activity (2.54 RU) on both camel and cow milk. The cheese samples showed significant oxidative and antibacterial activity.